Prevalence and Associated Factors of Metabolic Syndrome Among Patients with Severe Mental Illness at Hawassa, Southern-Ethiopia - Teshome T; Kassa DH; Hirigo AT (Diabetes, Metabolic Syndrome and Obesity, 2020)
Tesfaye Teshome,1 Dejene Hailu Kassa,2 Agete Tadewos Hirigo3 1Hawassa University, College of Medicine and Health Science, Faculty of Medicine, Physiology Unit, Hawassa City, Southern-Ethiopia; 2Hawassa University, College of Medicine and Health Science, Faculty of Health Science, School of Public Health, Hawassa City, Southern-Ethiopia; 3Hawassa University, College of Medicine and Health Science, School of Medical Laboratory Sciences, Hawassa City, Southern-EthiopiaCorrespondence: Tesfaye TeshomeHawassa University College of Medicine and Health Science, Faculty of Medicine, Physiology Unit, P.O. Box 1560, Hawassa City, Southern-EthiopiaTel +251-925-112625Email tesfayeteshome9@gmail.comBackground: Patients with severe mental disorders have a high risk of metabolic-related complications like metabolic syndrome (MetS), diabetes mellitus (DM), hypertension and lipid derangements, and these factors may predispose them to a high mortality rate. Data is very scarce regarding MetS among patients with severe mental illness in Ethiopia. Therefore, this study aimed to assess the prevalence of MetS and its associated factors among patients with severe mental illness.Methods: A cross-sectional study was conducted in Hawassa University Comprehensive Specialized Hospital from January to June 2019 among adult patients attending a psychiatric outpatient department, Southern Ethiopia. A systematic random sampling technique was used to select 245 study subjects. Socio-demographic and other data were collected using a structured questionnaire. Both the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) and International Diabetes Federation (IDF) guidelines were used to define MetS.Results: The prevalence of MetS was 24.5% and 26.9% by NCEP-ATP and IDF criteria respectively. In both definitions, females had significantly higher MetS when compared to males (31.4% vs 19.6%; p=0.03 by NCEP), and (34.3% vs 21.7%; p =0.03 by IDF), respectively. Duration > 5 years with mental illness indicated higher MetS when compared to duration ≤ 5 years (42.9% vs 19.9%, p=0.001; and 46.9% vs 21.9%, p< 0.0001) in NCEP and IDF, respectively. In addition, marital status [AOR (95% CI): 2.4 (1.1– 5.3)], and BMI [AOR (95% CI): 8.4(4.0– 17.6)], duration > 5 years with mental illness [AOR (95% CI): 2.8(1.2– 6.5)], and age > 40 years [AOR (95% CI): 2.7(1.2– 6.1)] were significantly associated factors of MetS by NCEP. While BMI, age > 40 years and duration > 5 years with mental illness were associated with MetS by IDF.Conclusion: Long-time experience with severe mental illness and antipsychotic therapy might predispose patients to metabolic complications with significant risks of cardiovascular events. Therefore, intensive screening of patients for MetS/components is required during follow-up based on national non-communicable diseases guideline. Besides, the proper intervention of patients concerning lifestyle changes and averting risk full behaviors is mandatory.Keywords: severe mental illness, antipsychotic agents, metabolic syndrome, Hawassa, Southern-Ethiopia